أخلاقيات المهنة ودورها في تعزيز المسؤولية الاجتماعية بالمؤسسات الإستشفائية- من وجهة نظر العاملين - بدر الدين, نبيل; خيشة, محمد علي (University of Eloued جامعة الوادي, 2023)
Abstract The objectives of the current study were to reveal the role of professional ethics among officials oriented towards employees by promoting social responsibility, the role of professional ethics among officials oriented towards senior management in promoting social responsibility, and the role of professional ethics among officials oriented towards the local community in promoting social responsibility within the hospital institution Omar Ben jilani in the state of El-Oued. To achieve the objectives of the study, the descriptive approach was used according to the method of a case study, and the study sample was determined by 35 individuals, and the questionnaire was the main tool for data collection. The current study reached the following results: • That the institution focus significantly contributes to the promotion of social responsibility on professional ethics directed towards the local community more than senior management and employees. • Promoting professional ethics and social responsibility within the hospital institution, Omar Ben Jilani, in the state of El-Oued, by a clear percentage. • The employee-oriented profession ethics promotes social responsibility at a high rate within the Omar Ben Jilani hospital in El-Oued state. • Professional ethics oriented towards senior management promote social responsibility at a very high rate within the Omar Ben Jilani hospital in El-Oued state. • The ethics of the profession oriented towards the local community promotes social responsibility at a very high rate within the hospital institution Omar Ben Jilani in the state of El-Oued.
" دراسة حالة بالمؤسسة العمومية الإستشفائية بالوادي- بن عمر الجيلاني-"
مذكرة ماستر في علم الاجتماع تخصص تنظيم وعمل
Keywords: أخلاقيات المهنة، L'éthique professionnelle, Professional ethics; المسؤولية الإجتماعية، Responsabilité sociale,Social Responsibility